2021
DOI: 10.1101/2021.12.22.473789
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HSP70-binding motifs function as protein quality control degrons

Abstract: Protein quality control (PQC) degrons are short protein segments that target misfolded proteins for degradation through the ubiquitin-proteasome system (UPS). To uncover how PQC degrons function, we performed a screen in Saccharomyces cerevisiae by fusing a library of flexible tetrapeptides to the C-terminus of the Ura3-HA-GFP reporter. The identified degrons exhibited high sequence variation but with marked hydrophobicity. Notably, the best scoring degrons constitute predicted Hsp70-binding motifs. When direc… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 83 publications
1
2
0
Order By: Relevance
“…Most notably, we find that the presence of the negatively charged side chains in Asp and Glu counteract degradation whereas the positively charged side chains in Lys and Arg have a more neutral effect. These results complement our recent observation that Hsp70 binding motifs, which are often hydrophobic and positively charged, can act as degrons 17, 27 . The effects of hydrophobic, positively and negatively charged residues are also validated by experiments that show that replacing hydrophobic residues with Glu in a degron can prevent degradation, whereas replacing the same amino acids with Arg has a substantially smaller effect 18 .…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Most notably, we find that the presence of the negatively charged side chains in Asp and Glu counteract degradation whereas the positively charged side chains in Lys and Arg have a more neutral effect. These results complement our recent observation that Hsp70 binding motifs, which are often hydrophobic and positively charged, can act as degrons 17, 27 . The effects of hydrophobic, positively and negatively charged residues are also validated by experiments that show that replacing hydrophobic residues with Glu in a degron can prevent degradation, whereas replacing the same amino acids with Arg has a substantially smaller effect 18 .…”
Section: Discussionsupporting
confidence: 90%
“…First, in the library we have screened we only vary 17-residue long peptides, and so our model only predicts degrons that fit within this length. More importantly, an unfolded or misfolded protein may have multiple degrons and we have previously shown that an increased number of exposed degrons lead to progressively lower abundance (Abildgaard et al, 2021). Thus, future work should quantify the relationship between the length and number of degrons and protein abundance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation